Dacryocystectomy as a treatment of chronic dacryocystitis in the elderly - Meireles, Mariana N. [UNESP]; Viveiros, Magda M.H. [UNESP]; Meneghin, Roberta L.F.S. [UNESP]; Galindo-Ferreiro, Alicia; Marques, Mariângela E.A. [UNESP]; Schellini, Silvana A. [UNESP] (Taylor & Francis, 2017)
To evaluate the dacryocystectomy (DCT) outcomes for chronic dacryocystitis in an elderly population over 70 years old. A retrospective chart review was performed for patients over 70 years old who were diagnosed with chronic dacryocystitis and underwent DCT at the Botucatu School of Medicine, UNESP, Brazil, from 2007 to July 2014. Data were collected about patient demographics, age, gender, previous nasal, or ophthalmic diseases, symptoms related to the lacrimal drainage system preoperatively and postoperatively, signs of enlargement of the lacrimal sac (regurgitation of secretion), and histopathologic evaluation. The study sample was comprised of 17 patients with an average age of 76.5 ± 8.5 years. The major complaint for all patients was tearing and 17.6% patients had an additional complaint of discharge. Regurgitation of secretion with lacrimal sac expression was present in 76.5% of patients. Postoperatively, 76.5% of the patients reported improvement of the initial complaint, likely due to the total excision of the lacrimal sac which removed the focal site of chronic infection. Epiphora persisted in 23.5% of patients, of whom 11.7% underwent successful lacrimal stent intubation. DCT for chronic dacryocystitis should be considered a primary procedure in individuals over 70 years old. This procedure has a much lower risk to these patients who often have associated comorbidities.
Keywords: Chronic dacryocystitis; dacryocystectomy; indication; surgery